The HeartWare Ventricular Assist Device (HVAD): A Single Institutional 10-Year Experience - Gyoten, Takayuki; Rojas, Sebastian V.; Fox, Henrik; Deutsch, Marc-Andre; Ruiz-Cano, Maria; Hakim-Meibodi, Kavous; Gummert, Jan F.; Morshuis, Michiel; Schramm, René (The Thoracic and Cardiovascular Surgeon, 2022)
Objectives The aim of this study was to analyze our 10-year experience with the HVAD in a real-world scenario in a high-volume German heart center.Methods We retrospectively analyzed outcomes of adults (≥18 years) with terminal heart failure (HF), who underwent HVAD implantation for durable LVAD therapy in our center between October 2009 and March 2020. Primary and secondary end points were all-cause death after implantation and LVAD-associated complications, respectively. We focused the distinct analyses on risk profiles at the time of implantation and implant strategies, i.e., bridge-to-transplant (BTT) or destination therapy (DT).Results A total of 510 patients were included, with 229 and 281 individuals in Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) level 1 (45%) and 2 to 4, respectively. Median follow-up was 26 months (IQR: 5–54 months). Overall survival at 1, 3, and 5 years after HVAD implantation was 66% (95% CI; 61.7–70%), 49.4% (95% CI; 44.9–53.8%), and 37.4% (95% CI; 32.8–42%), not censored for LVAD exchange, LVAD explantation, or heart transplantation. INTERMACS level 1 and peri-operative temporary right heart assistance were independent risk factors for survival. Survival was best in BTT patients undergoing heart transplantation at any time during follow-up. The INTERMACS level at time of HVAD implantation did not affect survival after heart transplantation. Freedom from the combined end point of any device-associated severe complication and death was 44.5% (95% CI; 40–48.8%) at 1-year after implantation.Conclusion The HVAD is a reliable pump for durable mechanical circulatory support even in high-risk patients. Still, heart transplantation outperforms durable MCS therapy for a superior long-term survival.
Keywords: left ventricular assist device; heart transplantation; survival; complications; HeartWare ventricular assist device